2017
DOI: 10.1074/mcp.ra117.000109
|View full text |Cite
|
Sign up to set email alerts
|

Dormancy in Embryos: Insight from Hydrated Encysted Embryos of an Aquatic Invertebrate

Abstract: Numerous aquatic invertebrates remain dormant for decades in a hydrated state as encysted embryos. In search for functional pathways associated with this form of dormancy, we used label-free quantitative proteomics to compare the proteomes of hydrated encysted dormant embryos (resting eggs; RE) with nondormant embryos (amictic eggs; AM) of the rotifer A total of 2631 proteins were identified in rotifer eggs. About 62% proteins showed higher abundance in AM relative to RE (Fold Change>3; = 0.05). Proteins belon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(48 citation statements)
references
References 128 publications
2
46
0
Order By: Relevance
“…Some candidates for these NADES were at higher abundance in AM in comparison with RE. Trehalose, with an established role in the formation of a glass at ambient temperatures was previously reported to occur at low levels in rotifer RE 31 ; transcriptome and proteome profiling studies revealed the occurrence of enzymes in the trehalose synthesis pathway 17,32,62 . Our current results generally indicate a higher abundance of trehalose in RE, suggesting a functional role for this metabolite in dormant RE, in contrast to a previous publication 31 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Some candidates for these NADES were at higher abundance in AM in comparison with RE. Trehalose, with an established role in the formation of a glass at ambient temperatures was previously reported to occur at low levels in rotifer RE 31 ; transcriptome and proteome profiling studies revealed the occurrence of enzymes in the trehalose synthesis pathway 17,32,62 . Our current results generally indicate a higher abundance of trehalose in RE, suggesting a functional role for this metabolite in dormant RE, in contrast to a previous publication 31 .…”
Section: Resultsmentioning
confidence: 99%
“…However, it was not detected in desiccated bdelloid rotifers and tardigrades 16,30 . Only small amounts of trehalose (0.35% of the dry weight) were found in rotifer RE 31 , although two transcripts encoding for trehalase-6-phophate synthase, and four trehalose phosphate synthase enzymes, were detected in rotifer RE 17,32 , suggesting its biosynthesis in rotifers.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations